2015
DOI: 10.1371/journal.pone.0133773
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Depletion Strategies for the Enrichment of Low-Abundance Proteins in Urine

Abstract: Proteome analysis of complex biological samples for biomarker identification remains challenging, among others due to the extended range of protein concentrations. High-abundance proteins like albumin or IgG of plasma and urine, may interfere with the detection of potential disease biomarkers. Currently, several options are available for the depletion of abundant proteins in plasma. However, the applicability of these methods in urine has not been thoroughly investigated. In this study, we compared different, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 45 publications
2
49
0
2
Order By: Relevance
“…All LC-MS/MS experiments were performed on the Dionex Ultimate 3000 UHPLC system coupled with the high resolution nano-ESI Orbitrap-Elite mass spectrometer (Thermo Finnigan, Bremen, Germany), as previously described (17). Briefly, 5 μl corresponding to 5 μg of the peptide mixture were analyzed on a Dionex Ultimate 3000 RSLS nanoflow system (Dionex™, Camberly, UK).…”
Section: Lc-ms/ms (Liquid Chromatography Coupled To Tandem Massmentioning
confidence: 99%
See 1 more Smart Citation
“…All LC-MS/MS experiments were performed on the Dionex Ultimate 3000 UHPLC system coupled with the high resolution nano-ESI Orbitrap-Elite mass spectrometer (Thermo Finnigan, Bremen, Germany), as previously described (17). Briefly, 5 μl corresponding to 5 μg of the peptide mixture were analyzed on a Dionex Ultimate 3000 RSLS nanoflow system (Dionex™, Camberly, UK).…”
Section: Lc-ms/ms (Liquid Chromatography Coupled To Tandem Massmentioning
confidence: 99%
“…Quantification analysis was performed at the peptide level as previously described (17). Only proteins being present in 75% of the samples in at least one group were further processed for quantification and statistical analysis (Mann-Whitney).…”
Section: Lc-ms/ms (Liquid Chromatography Coupled To Tandem Massmentioning
confidence: 99%
“…Efforts have been made in characterizing protein profile of biological samples such as placenta [17], urine [18] plants [19], etc. The techniques applied to this goal are diverse and include protein depletion and mass spectrometry [17,20], improved fractionation and purification methods [18], high-resolution NMR [21] among others.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, several fractionation methods for protein depletion are available but these approaches require relatively high amounts of starting material to ensure efficient enrichment of low-abundant proteins; otherwise, high-and medium-abundant proteins would not fully saturate their ligands and ultimately the elution would have the same profile as initial sample [28] [29].…”
Section: Sample Preparationmentioning
confidence: 99%
“…Studies have shown interactions with many cardiovascular drugs and calcium channel blockers [28]. PROP's metabolism involves multiple pathways in the cytochrome P-450 system (CYP2D6, 1A2, 2C19), co-administration with drugs that are metabolized, or affect the activity (induction or inhibition) of one or more of these pathways leading to clinically relevant drug interactions [29].…”
Section: Effects Of Propmentioning
confidence: 99%